A carnivorous sundew plant prefers protein over chitin as a source of nitrogen from its traps - Pavlovič, Andrej; Krausko, Miroslav; Adamec, Lubomír (Plant physiology and biochemistry, 2016)
Carnivorous plants have evolved in nutrient-poor wetland habitats. They capture arthropod prey, which is an additional source of plant growth limiting nutrients. One of them is nitrogen, which occurs in the form of chitin and proteins in prey carcasses. In this study, the nutritional value of chitin and protein and their digestion traits in the carnivorous sundew Drosera capensis L. were estimated using stable nitrogen isotope abundance. Plants fed on chitin derived 49% of the leaf nitrogen from chitin, while those fed on the protein bovine serum albumin (BSA) derived 70% of its leaf nitrogen from this. Moreover, leaf nitrogen content doubled in protein-fed in comparison to chitin-fed plants indicating that the proteins were digested more effectively in comparison to chitin and resulted in significantly higher chlorophyll contents. The surplus chlorophyll and absorbed nitrogen from the protein digestion were incorporated into photosynthetic proteins - the light harvesting antennae of photosystem II. The incorporation of insect nitrogen into the plant photosynthetic apparatus may explain the increased rate of photosynthesis and plant growth after feeding. This general response in many genera of carnivorous plants has been reported in many previous studies.
Keywords: Cattle; Animals; Chitin; skot; Plant chitinase; Nitrogen; listy rostlin; Biomass; Nitrogen Isotopes; chitin; sérový albumin hovězí; Photosynthesis; Pigments, Biological; Serum Albumin, Bovine; Plant Leaves; biologické pigmenty; Nitrogen uptake; Drosera; izotopy dusíku; zvířata; biomasa; Chlorophyll; Carnivorous plant; dusík